(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The banking sector is the backbone of economic development. When a bank fails in a country, it has a negative impact on other sectors. NPA stands for Non-Performing Assets and refers to loans that are not generating income for the bank. High levels of NPA can negatively impact bank profits. This paper aims to compare the non-performing assets (NPA) of private and public banks over the last six years.And show the bank with the highest and lowest NPA compared to others. It also seeks to identify the extent of control banks have over their NPAs. The study is descriptive in nature, and secondary data is used for analysis.